COMMODIFICATION OF RELIGIOUS SYMBOLS THROUGH THE PRACTICE OF ISLAMIC LIFESTYLE ON HIJABERS IN KEDIRI - Umi Hanik; A Zahid; Rista Aulia Sholikhah (Asosiasi Sosiologi Agama Indonesia (ASAGI), 2022)
Globalization not only affected the development of science and technology but also the socio-religious life of society. In this study, religious symbols are reproduced into a phenomenon in the form of a trend or Islamic lifestyle applied by Hijabers Kediri. This study was conducted with a qualitative descriptive method, with data collection carried out in 3 ways: observation, interviews, and documentation. The subjects of this study were the chairman and members who play an active role in the Hijabers Kediri community. Sources of data were in the form of primary and secondary data sources. This study was analyzed using the Theory of Consumption Society by Jean Baudrillard. So the results obtained are that the consumption community has been represented concretely by Hijabers Kediri through the Islamic Lifestyle that they applied, where hijab is a consumptive cultural lighter for Muslim women. It was no longer a religious symbol used to cover aurat as outlined in Islamic law. However, it is a fashionable need to use the hijab. The use of famous brands is carried out not based on need but an urge to do